2017
DOI: 10.1111/jorc.12200
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Healthcare Encounters Experienced by Patients With Chronic Kidney Disease

Abstract: Understanding patterns of healthcare encounters provides important information about the transition experiences of patients with CKD. Exploring ways to reduce the risks associated with transitions in care may prevent problems with home medication management, frequent emergency department visits and potentially avoidable hospitalisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Another explanation is the complexity of the study patient cohort, with all critical events recorded during this study deemed to be unavoidable. We found that respiratory distress was the most common trigger to both EDP and IPA compared to findings in other studies of patients with CKD [ 8 ] or cancer [ 54 ] where pain was more likely to trigger an EDP. Patients with advanced CKD will benefit from palliative care input to initiate end-of-life discussions and to help determine future goals of care [ 55 ] such as their preferred place of care and withdrawal from dialysis.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…Another explanation is the complexity of the study patient cohort, with all critical events recorded during this study deemed to be unavoidable. We found that respiratory distress was the most common trigger to both EDP and IPA compared to findings in other studies of patients with CKD [ 8 ] or cancer [ 54 ] where pain was more likely to trigger an EDP. Patients with advanced CKD will benefit from palliative care input to initiate end-of-life discussions and to help determine future goals of care [ 55 ] such as their preferred place of care and withdrawal from dialysis.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies identifying patterns in health service utilisation in those with CKD are limited by their retrospective design, reliance on various forms of administrative health and insurance data [ 8 , 11 , 33 ] and/or incomplete capture of individual patient-level data. These limitations are shared by previous Australian studies of service use near the end of life [ 34 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations